Native paddy cultivation: understanding of the practice and crop management among Sarawak's farmers - Abd Hamid, Izzah; Wan Yahaya, Wan Asrina; Rahim, Hairazi (Secholian Publication, 2022)
Native paddy is widely acknowledged for its authentic taste and fragrance but is often reported with low yield. Hence, the objective of this paper was to identify the practice and crop management of native paddy in Sarawak. About 56 targeted participants who actively cultivated native paddy were surveyed from January to June 2021. Our results have revealed their background and management contributed the most to the yield where no irrigation system, low fertiliser application, and the possibility of impurity seedlings become the significant constraints. Besides, unpredictable weather and long-distance travel to buy agricultural supplies worsened this problem. The participants apply fertiliser in low amounts compared to their cultivation areas (>2.5 ha), and those who mixed cropping will share the fertiliser with another crop. Paddy varieties such as Rotan (Wai), Biris, and others need a longer period of growth (5½ months) and are cultivated once a year. This showed unproductive production and a high infestation of pests and diseases. Therefore, we suggest intensive paddy cultivation by addressing the issues found in this study.